2017
DOI: 10.1080/15592324.2016.1273303
|View full text |Cite
|
Sign up to set email alerts
|

Environmental nitrate signals through abscisic acid in the root tip

Abstract: Roots respond to changes in environmental nitrate with a localized stimulation of ABA levels in the root tip. This rise in ABA levels is due to the action of ER-localized b-GLUCOSIDASE 1, which releases bioactive ABA from the inactive ABA-glucose ester. The slow rise in root tip ABA levels stimulates expression of nitrate metabolic enzymes and simultaneously activates a negative feedback loop involving the protein phosphatase, ABI2, which reduces nitrate influx via the AtNPF6.3 transceptor. The rise in root-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…This fact indicates that the SHA‐mediated increase in root ABA concentration also plays a relevant role in the root growth‐promoting action of SHA. These results are in line with Harris and Ondzighi‐Assoume () who showed the relevant role of root ABA in the modulation of root growth. Our results indicate that whereas some aspects of the SHA‐mediated effects on root development (lateral and adventitious root proliferation) and architecture (length of principal root) are expressed through IAA, NO, and ethylene signaling pathways (Mora et al, ), other aspects concerning the whole root growth involve ABA signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This fact indicates that the SHA‐mediated increase in root ABA concentration also plays a relevant role in the root growth‐promoting action of SHA. These results are in line with Harris and Ondzighi‐Assoume () who showed the relevant role of root ABA in the modulation of root growth. Our results indicate that whereas some aspects of the SHA‐mediated effects on root development (lateral and adventitious root proliferation) and architecture (length of principal root) are expressed through IAA, NO, and ethylene signaling pathways (Mora et al, ), other aspects concerning the whole root growth involve ABA signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Olaetxea et al () reported that SHA was able to increase Lp r through ABA‐dependent pathways, with this effect being essential for the enhancement of shoot growth. In this sense, recent studies have shown that root ABA affects root growth and architecture by interacting with some nitrate transporters (Harris & Ondzighi‐Assoume, ). Several studies have shown that HA with diverse origins increased the expression of nitrate transporters in different plant species (Olaetxea et al, and references there in).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the level of root‐tip‐localized ABA also negatively regulates the expression of the SCARECROW transcription factor gene, thus providing a sensitive mechanism for modulating root growth in response to environmental changes. [ 297 ] Together, these results indicate that ABA‐GE levels in plants and the ABA‐GE hydrolysis enzyme β ‐glucosidase 1 have significant functions in ABA catabolism.…”
Section: Aba Catabolismmentioning
confidence: 92%
“…Additionally, abscisic acid (ABA) and gibberellic acid (GA) are involved in P starvation signalling in plants (Baek et al ., 2017). ABA has also been implicated in the nitrate‐mediated signalling pathway for lateral root elongation (Harris and Ondzighi‐Assoume, 2017). In our study, two putative strigolactone esterase D14 genes (Traes_4BL_D05623E45, Traes_4BL_D62825306) involved in the strigolactone signalling pathway, and one GA 2‐oxidase 6 gene (Traes_1DS_125A395C1) was upregulated under P starvation condition at the later stage of colonization (Supporting Information Table S4).…”
Section: Biosynthesis Of Phytohormones and Secondary Metabolitesmentioning
confidence: 99%